Advances and Prospects for Whispering Gallery Mode Microcavities. Issue 9 (11th August 2015) - Yang, Shancheng; Wang, Yue; Sun, Handong
<x xml:space="preserve">Abstract</x> Microlasers have experienced tremendous development in the past decade and become an essential part in laser evolution, as miniature lasers provide strong optical confinement and feature greatly enhanced light–matter interactions. Among all the configurations, whispering gallery mode (WGM) microcavities and microlasers exhibit outstanding optical performances with high quality factors and small mode volumes, thus ensuring low lasing thresholds. In addition, some unique properties inherent to WGM cavities, like bi‐directional propagation and an evanescent field that spans several hundred nanometers across the boundary, can be exploited for novel applications. Therefore, designing and engineering innovative WGM microcavities and microlasers has attracted increasing research interest. The fundamentals and characteristics of WGM are introduced here, and then the developments and current status of WGM microcavities and microlasers are reviewed in terms of the evolution of fabrication techniques and built‐up materials. In particular, the melting of glassy materials in early studies, top‐down and bottom‐up approaches with semiconductors, coating structures, as well as flexible, soft microresonators in recent years are presented. Finally, the application prospects of microlasers including the wavelength manipulation, sensing and microresonator coupling, are discussed.